Cavitation-Enhanced Drug Delivery and Immunotherapy - Brandon Helfield; Shashank Sirsi; James Kwan; Michael Gray (MDPI AG, 2023)
Welcome to this special issue on Cavitation-Enhanced Drug Delivery and Immunotherapy-a rapidly evolving area that has been buoyed in recent years by the development of methods harnessing the activity of ultrasound-stimulated bubbles known as cavitation [...]